2020
DOI: 10.1001/jamaoto.2020.1346
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Prehabilitation—Supporting Recovery From Major Head and Neck Cancer Surgery

Abstract: Head and neck cancer (HNC) is the seventh most common type of cancer worldwide. 1 Surgery involving resection and free flap reconstruction is a mainstay of HNC treatment. Multimodal care pathways using Enhanced Recovery After Surgery (ERAS) guidelines have transformed perioperative care in HNC, 2 and the overall goal of ERAS is to achieve early functional recovery for patients undergoing major surgery. ERAS is a set of evidence-based recommendations that span preoperative, intraoperative, and postoperative car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Following the recommendation of the Society of Sarcopenia, Cachexia, and Wasting Disorders, sarcopenic patients should be instructed to undergo progressive resistance training two to three times a week to increase muscle mass and function. This can be self‐directed or under the instruction of a physical therapist 129–131 …”
Section: Resultsmentioning
confidence: 99%
“…Following the recommendation of the Society of Sarcopenia, Cachexia, and Wasting Disorders, sarcopenic patients should be instructed to undergo progressive resistance training two to three times a week to increase muscle mass and function. This can be self‐directed or under the instruction of a physical therapist 129–131 …”
Section: Resultsmentioning
confidence: 99%
“…Where feasible, this requires further consideration in future advancements of HNC-specific ERAS pathways. However, we believe that future research should also explore the benefits of physical activity in the waiting period before HNC surgery [26] and build on promising early evidence that postoperative exercise (in addition to standard physical therapy) reduces LOS [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been suggested that exercise physiologists could take on the role of early and progressive mobility specialists who reduces the burden on physical therapists and nurses 48 . An intervention supported by clinical exercise physiologists may be important in implementing tailored recommendations for physical activity, which is especially relevant for prehabilitation 49 . Objective measurement of physical activity via WATs before HNC surgery will enable remote monitoring of prehabilitation interventions (which extends to the use of a WAT across the pre and postoperative phases).…”
Section: Additional Avenues Of Research Using Wearable Activity Trackers For Patients Undergoing Surgery For Head and Neck Cancermentioning
confidence: 99%